Workflow Automation Engines: Driving Innovation in Cloud-Native and AI-Enhanced Business Processes - Siva Prakash Bikka, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article examines the evolution and impact of workflow automation engines in modern business environments, focusing on their integration with cloud-native technologies and artificial intelligence. The article explores how these engines serve as fundamental enablers of digital transformation, offering organizations enhanced operational efficiency, process consistency, and scalability. The article shows various industry applications across healthcare, financial services, e-commerce, manufacturing, and public sectors, demonstrating the versatile benefits of workflow automation. It analyzes emerging trends, including AI integration, low-code/no-code platforms, hyperautomation, and cloud-native optimization, while addressing strategic implementation considerations such as cloud infrastructure integration, AI decision point orchestration, scalability planning, and cross-platform standardization. Through extensive analysis of real-world implementations and industry data, the article highlights how workflow automation engines have revolutionized business processes, enabling organizations to achieve operational excellence while maintaining flexibility and adaptability in an increasingly digital business landscape.
Keywords: Artificial Intelligence Integration; Cloud-Native Technologies; Digital Transformation; Process Optimization; Workflow Automation Engines